A comparative study of in-service and pre-service teachers’ beliefs about the urgency of compulsory English in Indonesian primary schools within the Merdeka Curriculum - Nely Arif; Robi Soma; Reny Heryanti; Habizar Habizar (EduLite: Journal of English Education, Literature and Culture, 2026)
The introduction of compulsory English in Indonesian primary schools has become an important issue in English language education. Although early English learning is widely supported, the implementation of the Merdeka Curriculum and the government's 2027 mandate raises questions about school readiness and teacher preparedness. This study compares the beliefs of in-service and pre-service teachers regarding the urgency of English as a compulsory subject in primary schools and examines how these beliefs relate to policy implementation, professional readiness, and curriculum interpretation. Using a qualitative descriptive design, the study involved ten purposively selected participants in Jambi Province, Indonesia: five in-service teachers and five pre-service teachers. Data were collected through semi-structured interviews and reflective narratives and analysed using thematic analysis. Three themes emerged. First, both groups strongly affirmed the urgency of early English learning, citing digital exposure, the developmental advantages of early language learning, and the prevention of future academic gaps. Second, although participants supported the 2027 compulsory English policy, they expressed concerns about unequal school readiness, teacher shortages, and limited educational resources, particularly in rural areas. Third, both groups acknowledged gaps in professional readiness; however, teachers emphasized pedagogical and institutional challenges, whereas pre-service teachers highlighted limited confidence and insufficient preparation for Teaching English to Young Learners (TEYL). Overall, both groups supported compulsory English in primary schools but expressed concerns about school readiness, teacher competence, and unequal educational resources, indicating that successful implementation requires comprehensive institutional support.